Drop Height Impacts the Lower Limb Elastic Energy’s Utilization for Male High Jumpers: A Experimental Research from Biomechanics - Zehao Tong; Wenjia Chen; Hang Xu; Feng Zhai (Applied Bionics and Biomechanics)
The study’s objective is to clarify the influence of drop height on elastic energy’s utilization of the lower extremity, to indicate the correlations between elastic energy’s utilization and personal best, and to determine the optimal loading height for elastic energy’s utilization for male high jumpers. Ten male athletes who belong to high jump events work out the drop jump at different drop heights (0.3 m, 0.45 m, 0.6 m, and 0.75 m). Two AMTI force platforms were used to capture the dynamics data for the lower extremity. Drop height has obvious influence on utilization ratio for elastic energy (P<0.01). The utilization ratio of elastic energy has no note correlation with personal best (r=0.149, P>0.05). In this study, the optimal loading height for utilization ratio of elastic energy was 0.75 m. The optimal loading height can be determined in terms of the elastic energy utilization ratio for each high jumper to enhance their training effects.